Large-N correlator systems for low frequency radio astronomy - Foster, G (2013)
Low frequency radio astronomy has entered a second golden age driven by the development of a new class of large-N interferometric arrays. The low frequency array (LOFAR) and a number of redshifted HI Epoch of Reionization (EoR) arrays are currently undergoing commission and regularly observing. Future arrays of unprecedented sensitivity and resolutions at low frequencies, such as the square kilometer array (SKA) and the hydrogen epoch of reionization array (HERA), are in development. The combination of advancements in specialized field programmable gate array (FPGA) hardware for signal processing, computing and graphics processing unit (GPU) resources, and new imaging and calibration algorithms has opened up the oft underused radio band below 300 MHz. These interferometric arrays require efficient implementation of digital signal processing (DSP) hardware to compute the baseline correlations. FPGA technology provides an optimal platform to develop new correlators. The significant growth in data rates from these systems requires automated software to reduce the correlations in real time before storing the data products to disk. Low frequency, widefield observations introduce a number of unique calibration and imaging challenges. The efficient implementation of FX correlators using FPGA hardware is presented. Two correlators have been developed, one for the 32 element BEST-2 array at Medicina Observatory and the other for the 96 element LOFAR station at Chilbolton Observatory. In addition, calibration and imaging software has been developed for each system which makes use of the radio interferometry measurement equation (RIME) to derive calibrations. A process for generating sky maps from widefield LOFAR station observations is presented. Shapelets, a method of modelling extended structures such as resolved sources and beam patterns has been adapted for radio astronomy use to further improve system calibration. Scaling of computing technology allows for the development of larger correlator systems, which in turn allows for improvements in sensitivity and resolution. This requires new calibration techniques which account for a broad range of systematic effects. And, a deep integration between DSP hardware and software data reduction into a single backend.